Ecologizing economic sociology: A tale of (dis)embedding? - Ute Tellmann (economic sociology. perspectives and conversations, 2024)
The destruction of existing modes of exchange and production in many places is a likely outlook for a world that is unable to deal adequately with its dependency on a "critical zone" of livability (Latour and Weibel 2020). In the Anthropocene, food and water security will probably be more difficult to achieve; social and political protection against loss through floods, heatwaves, and hurricanes will be more costly; and the provisioning of goods, services, and public health will become more demanding (Elliot 2021; Thomas, Williams, and Zalasiewicz 2020, 12). Given the rapidness with which the tipping points of the earth system seem to be reached, a considerable reinvention of economies appears to be imminent in the near future.
Keywords: 300